2007
DOI: 10.1080/15287390701384791
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Risk Assessment of Cryptosporidium Exposure Among Baltimore Urban Anglers

Abstract: In some urban settings, recreational fishing in industrialized waterways may pose a substantial health risk due to the presence of pathogenic microbes such as Cryptosporidium, a pathogen that produces a moderate to fatal gastrointestinal illness in humans. This pilot study examined the risk of exposure to Cryptosporidium based on fish samples and hand wash samples taken from urban anglers. Information regarding fishing frequency and consumption were also collected through an interview questionnaire to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…10 of 18 (56%) hand samples and 7 of 28 (25%) fish samples were positive for Cryptosporidium. No genotyping was conducted to determine what species or genotypes of Cryptoporidium were present but the authors concluded that the mean probability of infection with Cryptosporidium was relatively high (Roberts et al, 2007).…”
Section: Cryptosporidium In Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…10 of 18 (56%) hand samples and 7 of 28 (25%) fish samples were positive for Cryptosporidium. No genotyping was conducted to determine what species or genotypes of Cryptoporidium were present but the authors concluded that the mean probability of infection with Cryptosporidium was relatively high (Roberts et al, 2007).…”
Section: Cryptosporidium In Fishmentioning
confidence: 99%
“…Experimental transmission of C. parvum into rainbow trout revealed no life-cycle stages of A recent study examined the risk of exposure to Cryptosporidium based on fish samples and hand wash samples taken from Baltimore urban anglers (Roberts et al, 2007). A total of 46 fish and hand wash samples were collected from several popular angling locations in the Baltimore Metropolitan area.…”
Section: Cryptosporidium In Fishmentioning
confidence: 99%
“…There is no published information on contamination of crabs with Cryptosporidium, a waterborne pathogen commonly reported from coastal waters (3,6). However, our previous study demonstrated mechanical passage of C. parvum oocysts via handling of fish caught in urban watersheds to the hands of recreational anglers (16). The purposes of the present study were to determine if commercially harvested Atlantic blue crabs (Callinectes sapidus), which are widely consumed, can serve as a vehicle for infectious waterborne oocysts of C. parvum and if the handling of crabs collected from Cryptosporidium-contaminated water can result in oocyst transfer to the handler's hands.…”
mentioning
confidence: 99%
“…The present study indicates that handling and storage of edible crabs harvested from contaminated waters may represent an occupational health risk for cryptosporidiosis. Proper hand washing is effective in the removal of C. parvum oocysts (16).…”
mentioning
confidence: 99%
“…7 Primarily, most studies have defined risk-associated recreational activities for only two broad categories: swimming or nonswimming, and focused on beaches and marine environments rather than freshwater bodies. 8,9 However, there are a few exceptions; Cryptosporidium risk was assessed for urban anglers through questionnaires, hand washing and fish sampling 10 and risk of gastrointestinal (GI) illness among surfers was researched by Stone and other authors. 11 Limited contact recreational activities, such as boating, fishing, kayaking, wading, canoeing, jet skiing and so on, have not been fully researched, because it is assumed that many of these activities have lower rates of exposure to water and thus to gastrointestinal pathogens compared with swimming.…”
Section: Introductionmentioning
confidence: 99%